Rehydration behaviour of spray-dried micellar casein concentrates produced using microfiltration of skim milk at cold or warm temperatures. (June 2018) - Crowley, Shane V.; Burlot, Esther; Silva, Juliana V.C.; McCarthy, Noel A.; Wijayanti, Heni B.; Fenelon, Mark A.; Kelly, Alan L.; O'Mahony, James A.
Abstract: Microfiltration (MF) of skim milk, when combined with diafiltration (DF), facilitates the manufacture of liquid micellar casein concentrate (MCC), which can be spray-dried into high-protein (≥80% protein, dry-basis) powders. MCC powders rehydrate slowly, which is typically considered a defect by end-users. This study compared the impact of cold (<10 °C) or warm (50 °C) MF/DF on the rehydration characteristics of MCC powders (MCCcold and MCCwarm, respectively). The wetting properties of the MCC powders, measured using optical tensiometry, were found to be equivalent. However, pronounced differences in dispersion characteristics were measured, and, after 90 min rehydration at 50 °C, liberated casein micelles accounted for only 7.5% of total particle volume in MCCwarm compared with 48% in MCCcold . Due to its superior dispersion characteristics, MCCcold yielded 50–60% less sediment during analytical centrifugation experiments. Cold MF/DF may improve the solubility of MCC powders by accelerating the release of casein micelles from powder particles during rehydration.